Carboxylic‐Phosphoric Anhydrides as Direct Electrophiles for Decarbonylative Hirao Cross‐Coupling of Carboxylic Acids: DFT Investigation of Mechanistic Pathway. Issue 7 (20th February 2023) - Liu, Chengwei; Xing, Yang‐Yang; Zhou, Tongliang; Chen, Tieqiao; Hong, Xin; Szostak, Michal
Abstract: In this anniversary issue, we present a DFT study of the mechanism of decarbonylative Hirao cross‐coupling of carboxylic‐phosphoric anhydrides to afford aryl phosphonates. Traditionally, the direct activation of carboxylic acids to participate in decarbonylative couplings is performed in the presence of carboxylic acid anhydride activators. We discovered that direct dehydrogenative decarbonylative phosphorylation of benzoic acid can be performed in high yield via dehydrogenative and decarbonylative coupling in the presence of phosphite as dual activating and nucleophilic reagent, enabling direct decarbonylative phosphorylation. Control studies demonstrated that carboxylic‐phosphoric anhydride (acyl phosphate) is an intermediate in this process. DFT studies were conducted to gain insight into this decarbonylative process and compare the selectivity of C−O and P−O bond activations. Considering the utility of ubiquitous carboxylic acids, this alternative activation pathway may find applications in decarbonylative coupling of carboxylic acids for the synthesis of valuable molecules in organic synthesis. Abstract : We report a DFT study of the mechanism of decarbonylative Hirao cross‐coupling of carboxylic‐phosphoric anhydrides (acyl phosphates) to afford aryl phosphonates. Direct dehydrogenative decarbonylative phosphorylation of benzoic acid can be performed in high yield via decarbonylative coupling in the presence of phosphite as dual activating and nucleophilic reagent. DFT studies were conducted to gain insight into this decarbonylative process and compare the selectivity of C−O and P−O bond activations.